Estrogen Regulates Glucose Metabolism in Cattle Neutrophils Through Autophagy - Wang, Xinbo; Zhang, Yuming; Li, Yansong; Tang, Mingyu; Deng, Qinghua; Mao, Jingdong; Du, Liyin (Frontiers in Veterinary Science, 2021)
Hypoglycemia resulting from a negative energy balance (NEB) in periparturient cattle is the major reason for a reduced glycogen content in polymorphonuclear neutrophils (PMNs). The lack of glycogen induces PMNs dysfunction and is responsible for the high incidence of perinatal diseases. The perinatal period is accompanied by dramatic changes in sex hormones levels of which estrogen (17β-estradiol, E2) has been shown to be closely associated with PMNs function. However, the precise regulatory mechanism of E2 on glucose metabolism in cattle PMNs has not been elucidated. Cattle PMNs were cultured in RPMI 1640 with 2.5 (LG), 5.5 (NG) and 25 (HG) mM glucose and E2 at 20 (EL), 200 (EM) and 450 (EH) pg/mL. We found that E2 maintained PMNs viability in different glucose conditions, and promoted glycogen synthesis by inhibiting PFK1, G6PDH and GSK-3β activity in LG while enhancing PFK1 and G6PDH activity and inhibiting GSK-3β activity in HG. E2 increased the ATP content in LG but decreased it in HG. This indicated that the E2-induced increase/decrease of ATP content may be independent of glycolysis and the pentose phosphate pathway (PPP). Further analysis showed that E2 promoted the activity of hexokinase (HK) and GLUT1, GLUT4 and SGLT1 expression in LG, while inhibiting GLUT1, GLUT4 and SGLT1 expression in HG. Finally, we found that E2 increased LC3, ATG5 and Beclin1 expression, inhibited p62 expression, promoting AMPK-dependent autophagy in LG, but with the opposite effect in HG. Moreover, E2 increased the Bcl-2/Bax ratio and decreased the apoptosis rate of PMNs in LG but had the opposite effect in HG. These results showed that E2 could promote AMPK-dependent autophagy and inhibit apoptosis in response to glucose-deficient environments. This study elucidated the detailed mechanism by which E2 promotes glycogen storage through enhancing glucose uptake and retarding glycolysis and the PPP in LG. Autophagy is essential for providing ATP to maintain the survival and immune potential of PMNs. These results provided significant evidence for further understanding the effects of E2 on PMNs immune potential during the hypoglycemia accompanying perinatal NEB in cattle.